Relasi Sistem Kekerabatan pada Arsitektur Tradisional di Desa Prapau Semende Sumatra Selatan - Syahfira Dwinda; Christina Gantini; Johannes Adiyanto (Arsir: Jurnal Arsitektur, 2024)
Traditional architecture is a cultural heritage resulting from the lives of traditional communities, encompassing both art and architectural knowledge. Similar to traditional architecture in many other regions of the Indonesian archipelago, traditional Semende architecture represents cultural heritage with variations in function, ornamentation, and form, often referred to as "Rumah Baghi." In daily life, the Semende indigenous community has established a robust inheritance law, deeply influenced by their kinship system. Notably, they place special emphasis on the eldest daughter's position as a principle within their customary concept known as "Tunggu Tubang." This kinship system distinguishes them from other cultures and imparts a unique characteristic to Semende's traditional architecture. This research aims to examine how the Tunggu Tubang kinship system influences the physical manifestation of Semende's traditional architecture. The research employs a qualitative descriptive methodology, involving data collection through field observations, interviews, and relevant literature studies. The findings reveal that within the Semende indigenous society, the Tunggu Tubang kinship system is vividly reflected in the architecture. The spatial arrangement within the Rumah Baghi signifies social structure and hierarchy, exterior ornamentation symbolizes the characteristics of matrilineal kinship, and traditional architecture reflects the principles of robust matrilineal inheritance.